2005
DOI: 10.1002/pip.602
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of thin‐film solar cell temperature coefficients for space applications

Abstract: At present, commercially available thin-film photovoltaic cells are evaluated for terrestrial applications. To apply thin-film photovoltaic cells for space applications, the assessment of the solar cell performance must be conducted in simulated space conditions. We investigated the temperature coefficients of the I-V characteristics of thinfilm amorphous silicon (a-Si) solar cells manufactured by Uni-Solar and Iowa Thin Film Technologies, and CuInGaSe 2 (CIGS) solar cells manufactured by MicroSat Systems with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 3 publications
1
17
0
Order By: Relevance
“…Extremely low temperatures (ranging from 220 to 290 K) are inevitable for photovoltaic technologies applied in near space or polar regions. Often in this temperature regime, the temperature coefficients are negative in conventional solar cells 25 but not yet clear in perovskite photovoltaics. Rapid progress has been witnessed to verify the operational feasibility of perovskite solar cells at low temperatures.…”
Section: Context and Scalementioning
confidence: 99%
See 1 more Smart Citation
“…Extremely low temperatures (ranging from 220 to 290 K) are inevitable for photovoltaic technologies applied in near space or polar regions. Often in this temperature regime, the temperature coefficients are negative in conventional solar cells 25 but not yet clear in perovskite photovoltaics. Rapid progress has been witnessed to verify the operational feasibility of perovskite solar cells at low temperatures.…”
Section: Context and Scalementioning
confidence: 99%
“…Photovoltaic devices for space applications have strict requirements, including high PCE with high specific power and specific volume, tolerance of space radiation damage, and stable performance through thermal cycling. 25 Perovskite solar cells have proven most of the advantages of high specific power and impressive mechanical flexibility. 26 Also, originating from the ionic nature of perovskites, these cells have shown improved tolerance against high-energy proton or electron irradiation as compared to conventional photovoltaics.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, integrating mild thermocatalysis into photocatalysis should be promising for utilizing idle IR energy, which is helpless in driving most photocatalysis because of the energy limit. However, IR-induced solar heating is generally repulsive in photocatalysis, as it usually leads to severe lattice vibration, damaging the photon-to-electron conversion [20]. Recently, we proposed a feasible strategy to address above IR-related contradiction, by integrating solid state ionics into photocatalysis [21].…”
Section: Introductionmentioning
confidence: 99%
“…It has been observed that the three most widely commercialized thin-film solar cells such as α-Si, CdTe and copper indium gallium selenide, the T C value is negative. 37,38 Although, they are highly effective in large scale operation. Negative T C value normally implies that with the increase of temperature, the parameter of interest will decrease, which can affect the performance of solar cell in a hot climate.…”
Section: Introductionmentioning
confidence: 99%